Collaborative Governance Model in Digital Innovation-Based Health Malpractice Law Enforcement - Mochamad Nu’aim Qomarudin; Ika Sartika (Solo International Collaboration and Publication of Social Sciences and Humanities, 2026)
Objective: This study aims to formulate a Collaborative Governance model for medical malpractice law enforcement leveraging digital innovation to enhance inter-agency coordination, legal certainty, and legal protection for both patients and healthcare professionals. Theoretical framework: The study is grounded in the concepts of Collaborative Governance and digital transformation in public administration, serving as a foundation for establishing effective, transparent, and accountable cross-sector coordination. Literature review: Previous studies have generally focused on litigation mechanisms, legal protections for healthcare professionals, and the role of Professional Disciplinary Councils; however, they have yet to integrate collaborative governance with digital innovation into a unified law enforcement model. Method: The study employs a normative-juridical approach with qualitative methods, utilizing a literature review of legislation, scholarly works, and secondary data analyzed through an interactive process. Results: Findings indicate that the low resolution rate of medical malpractice cases stems from weak inter-agency coordination, divergent perspectives regarding the evidentiary process, and a lack of integrated information systems. The study produces a model comprising five stages: digital reporting, collaborative verification, joint investigation, dispute resolution, and data-driven evaluation. Implications: This model has the potential to improve coordination effectiveness, transparency, accountability, and legal certainty in the handling of medical malpractice cases. Novelty: The research offers a conceptual model that integrates Collaborative Governance, the authority of Professional Disciplinary Councils, and digital innovation into a law enforcement system that is more responsive, integrated, and adaptive.